Boron and nitrogen doping in graphene: an experimental and density functional theory (DFT) study - Kaykilarli, Cantekin; Uzunsoy, Deniz; Parmak, Ebru Devrim Sam; Fellah, Mehmet Ferdi; Cakir, Ozgen Colak (IOP PUBLISHING LTD, 2020)
Boron (B) and Nitrogen (N) doped few layer graphene (BNG) is directly synthesized via electric arc discharge (EAD) method. NH3 and BCl3 gas mixtures are used in the synthesis atmosphere. Raman spectroscopy is used to determine graphene's purity and number of layers. The investigation of structure and morphology of pristine graphene and BNG are carried out via Transmission Electron Microscopy (TEM). The presence of B and N in the structure of graphene is detected by Energy Dispersive X-ray Spectroscopy (EDS) analysis. Elemental mapping show that N and B are distributed homogeneously in the graphene structure. It is observed that doping process did not affect the positions of the D, G and 2D bands in the Raman spectroscopy. The effect of doping on the number of layers of graphene is found negligible. TEM results exhibit that pristine graphene and BNG have 5 to 6 layers. Besides, the theoretical calculations based on Density Functional Theory (DFT) are employed to support experimental studies. Theoretical results based on DFT showed that bonding of B and N is favorable.
Keywords: boron; nitrogen; doped; graphene; electric arc discharge; DFT; FEW-LAYERED GRAPHENE; DOPED GRAPHENE; DISCHARGE; EFFICIENT; NANOMATERIALS; Science & Technology - Other Topics; Materials Science; Physics